2011
DOI: 10.1002/fuce.201100041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Humidification on the Membrane Electrode Assembly of Proton Exchange Membrane Fuel Cells at Relatively High Cell Temperatures

Abstract: This study focuses on the performances of proton exchange membrane fuel cells (PEMFCs) at 80 and 90 °C with feeds of varying degrees of humidification. The results show that ohmic resistance of the solid electrolyte decreases as the current density is raised because of the back diffusion of liquid water, that is, generated in the cathode active layer. On the other hand, severe liquid water accumulation occurs at high current densities, which hinders the oxygen transport in the cathode gas diffusion layer (GDL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The Equation (4.13) predicts that the diameter is independent of the current density or gas diffusivity. The measured Nyquist plots reported in literature show that the diameter of this arc remains unchanged in different current densities [15,20,46,112,114,[183][184][185][186][187][188]190], temperatures [189], torques [66,112], humidification levels [20,189], cathode gas concentrations [34,184], flooding or dehydration conditions [24,91,106,182], starvation [189] and break-in process [112]. The impedance measurements presented in Section 4.3 also show that this arc remains unchanged in different operating temperatures, current densities and anode and cathode relative humidities.…”
Section: High Frequency Arcmentioning
confidence: 63%
See 2 more Smart Citations
“…The Equation (4.13) predicts that the diameter is independent of the current density or gas diffusivity. The measured Nyquist plots reported in literature show that the diameter of this arc remains unchanged in different current densities [15,20,46,112,114,[183][184][185][186][187][188]190], temperatures [189], torques [66,112], humidification levels [20,189], cathode gas concentrations [34,184], flooding or dehydration conditions [24,91,106,182], starvation [189] and break-in process [112]. The impedance measurements presented in Section 4.3 also show that this arc remains unchanged in different operating temperatures, current densities and anode and cathode relative humidities.…”
Section: High Frequency Arcmentioning
confidence: 63%
“…The measured Nyquist plots of the PEM fuel cells in different operating conditions reported in literature include one arc [112,182], two distinguishable arcs [20,24,34,66,91,112,[183][184][185][186][187][188][189], or three clearly distinguishable arcs [15,20,46,114,190]. If the time constants of two adjacent arcs are close, they become convoluted and make one arc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To better understand hydration effects on durability, characterization of PEMs under liquid water saturation as an extreme exposure condition is necessary. The effect of hydration on the mechanical properties of PEMs has received extensive investigation [6][7][8][9][10][11][12][13][14]. Kusoglu et al [8] simulated the mechanical response of the membrane under humidity cycles and found that the membrane response strongly depends on the swelling anisotropy.…”
Section: Introductionmentioning
confidence: 99%
“…The deformable MEA, fabricated in a novel configuration, can be constrained in a limited space for both stationary and portable power sources [4][5][6][7]. One of the major design considerations is the water flooding in the MEA, arising from the blockage of gas diffusion layer by the generated water in cathode catalyst layer [8,9].…”
Section: Introductionmentioning
confidence: 99%